Artistic integrity in weapon-shaped hybrid musical instruments: the alutista project in Indonesian contemporary performance - Nanang Rahmat Hidayat (Gelar: Jurnal Seni Budaya, 2025)
The growth of contemporary music videos and performance art has encouraged the use of musical instruments as both sound sources and strong visual symbols. Existing studies on interdisciplinary performance discuss collaborations between musicians and visual artists, but rarely examine weapon-shaped hybrid instruments as integrated sound–visual media that must maintain artistic integrity. This article analyses how artistic creative integrity is achieved in the design and use of Alutista, a series of weapon-shaped hybrid musical instruments created by Nanang Garuda for Indonesian music videos and contemporary performances. The research adopts a qualitative descriptive approach combining visual observation, content analysis of 24 Alutista instruments documented on social media and performance videos, and thematic coding of form, sonic function, and performative role; in this study, artistic creative integrity is operationalized as the alignment between conceptual intention, visual design, and musical–performative function. The analysis identifies three main patterns of integrity: the symbolic transformation of weapons into instruments of peace; the interdependence between industrial visual aesthetics and metallic timbre; and the choreography of performers’ bodies with the instruments, which produces multisensory narratives that bind sound, image, and gesture into a single composition. Theoretically, the study extends debates on artistic integrity and experimental instrument design by proposing weapon-shaped hybrid instruments as cross-media objects that merge material ecology, symbolism, and performance; practically, it offers a design and staging model for artists and directors who seek to develop music videos and performances that balance visual spectacle with coherent sonic and conceptual expression.